7T locus coeruleus imaging correlates of apathy and cognition in patients with Parkinson's disease and progressive supranuclear palsy. (1st February 2022) - Ye, Rong; O'Callaghan, Claire; Rua, Catarina; Hezemans, Frank H.; Holland, Negin; Malpetti, Maura; Jones, P. Simon; Passamonti, Luca; Rowe, James B.
Abstract: Background: Apathy is a common neuropsychiatric feature of both Parkinson's disease and progressive supranuclear palsy (PSP) (Aarsland, et al., 2001). Early neuropathology in the locus coeruleus (LC) and consequent noradrenergic deficiency are proposed to be key contributors to the pathogenesis of apathy (Passamonti et al., 2018). Here we test the hypothesis that in vivo LC integrity measured by ultra‐high field 7T‐MRI is predictive of apathy in Parkinson's disease and PSP. Method: Sixty‐three participants aged 50‐80 years were recruited: 25 people with idiopathic Parkinson's disease, 14 patients with PSP Richardson's syndrome and 24 age‐ and sex‐matched healthy controls (HC). Patients underwent clinical assessments for apathy, impulsivity, global cognition, motor severity, mood and sleep (Figure 2A&B). The LC was measured in vivo using a sensitive magnetisation transfer (MT) weighted sequence with ultra‐high 7T‐MRI (0.1mm 3 voxels). The contrast‐to‐noise ratio of an atlas‐based signal was used to estimate the LC structural integrity (Ye et al., 2021). The LC integrity was correlated with clinical assessments. To estimate the spatial extent of the correlation within LC, voxelwise analyses used FSL randomise for localising the group differences and the clinical correlations. Result: Reduced LC integrity was observed along the rostrocaudal axis for both PD and PSP patients, most prominently in the caudal subregion (Figure 1A‐D). This was confirmed by significant voxelwise comparisons between the patient groups and controls (HC>PD, right caudal LC, 37 voxels; HC>PSP, bilateral caudal LC, 206 voxels; FWE‐corrected p <0.05), Figures 1E&F. Patients with PSP and PD showed similar levels of LC degeneration relative to controls, but this was more spatially widespread in PSP. The variability of LC integrity in both disease groups was associated with ACER, MoCA and apathy (Figure 2C&D). Distinctive spatial patterns were identified for the correlations, with the caudal LC consistently associated with cognitive impairment and apathy. Conclusion: Reduced LC integrity was confirmed in both PD and PSP using in vivo 7T‐MRI. LC degeneration, particularly in the caudal subregion, was associated with apathy and cognitive impairment. Our results suggest, noradrenergic therapies may be beneficial in targeting cognitive and behavioural features of Parkinson's disease and PSP.